Percutaneous cannulation for cardiopulmonary bypass in robotic mitral valve surgery with zero groin complications. Issue 2 (19th October 2021) - Bastopcu, Murat; Senay, Sahin; Güllü, Ahmet Ü.; Kocyigit, Muharrem; Alhan, Cem
Abstract: Introduction: Robotic valve surgery utilizes the femoral vessels to set up cardiopulmonary bypass (CPB) which translates to groin wound and lower extremity vascular complications. A less invasive technique is a totally percutaneous bypass using vascular closure devices (VCDs) with concerns for lower limb ischemia and arterial stenosis. Since April 2018, we have adopted the standard use of total percutaneous CPB in our robotic mitral cases. We report our institutional results with this technique. Methods: All consecutive patients who underwent robotic mitral valve surgery between April 2018 and December 2020 in our institution were included in our study. Hospital database data on demographics, operative variables, and surgical outcomes were recorded and analyzed. Results: Robotic mitral valve surgeries were performed on 32 consecutive patients (mean age 57.2 ± 14.8) between April 2018 and December 2020. None of our patients developed an infection at any site. Seroma, hematoma, or pseudoaneurysm were not observed at puncture sites. Surgical repair of the femoral vessels or an additional VCD was not necessary for any of our patients. Patients were followed up for a mean duration of 23.5 months. Our patients did not present with a late wound infection, a seroma, or a pseudoaneurysm, nor had complaints of limb ischemia or claudication. Conclusion: Total percutaneous bypass is the least invasive method of establishing extracorporeal circulation for cardiac surgery and can be performed with excellent results. The benefits of robotic surgery can be expanded with better results in groin cannulation by the adoption of total percutaneous CPB.